The futile debate over a multilateral framework for investment - Axel Berger (Columbia University, Vale Columbia Center on Sustainable International Investment (VCC), 2013)
A multilateral framework for investment (MFI) is not suitable for effectively solving the most pressing challenges in the current international investment regime. It would be more promising to tackle these challenges in the context of regional co-operation, supplemented by co-ordination efforts on the global level.
Keywords: 330